Hyperfiltration can be detected by transcutaneous assessment of glomerular filtration rate in diabetic obese mice: research article - Hettler, Steffen Andreas; Picascia, Tiziana; Pastene, Diego O.; Vajpayee, Srishti; Perciaccante, Rossana; Yard, Benito A.; Gretz, Norbert; Krämer, Bernhard (American journal of physiology. Cell physiology, 2023)
Download figureDownload PowerPoint
Online veröffentlicht: 13. November 2023
Gesehen am 09.04.2024